The Effectiveness of Obstetric Emergency Interventions in Enhancing Mother and Fetal Well-Being: A Systematic - Bhekti Imansari; Ida Nurhidayah; Ai Rahmawati; Risang Pawestri; Camilie G. Hemedes (Journal of Nursing Care, 2023)
An obstetric emergency is a condition that can threaten the life of a pregnant woman and the fetus, which occurs during pregnancy, childbirth and the puerperium. This review Â Â aimed to analyze the effectiveness of emergency obstetric interventions based on previous studies. The study was a systematic review carried out in seven stages through three databases from Ebsco, Pubmed and Proquest. The keywords used were (pregnant women) AND (emergency intervention) AND (nursing OR nurse) NOT (systematic review). The inclusion criteria in this study were: full-text, peer review, English, articles for the last five years, subject: nursing, nurses, emergency medical care, nursing care, emergency services, and document type: articles. Based on the search database, 10,496 papers were obtained, 733 documents that matched the inclusion criteria and seven papers that fit the theme were obtained. The result that based on the initial stage of the literature search, four interventions were adequate, including ACLS training, multidisciplinary management, making coloured ribbons for premature pregnancy detection, and maternal near-miss detection tools. Interventions with less effective based on statistical test results were supportive care, home visits with IPV (intimate partner violence) interventions, and administration of CPR, defibrillation, ETT insertion, and administration of epinephrine. Nurses still carry out a few emergency developmental interventions. It is necessary to develop engagement interventions related to maternal emergencies to improve the welfare of mothers and babies. Further study is needed to strengthen the evidence base of innovative interventions for specific obstetric emergencies.